Social media as a tourism promotion tool: the case of @thelodgemaribaya - Ira Purwitasari; Finy Fitrya Basarah; Anggun Putri Dewanggi I.B (Faculty of Communications Science, Dr. Soetomo University, 2024)
This research examined how @TheLodgeMaribaya utilized Instagram as a tool for tourism promotion in West Java, Indonesia through the use of AISAS concept (Attention, Interest, Search, Action, Share). In the digital era, social media users often seek out ‘Instagrammable’ locations that capture their Attention, spark Interest, then lead them to Search for further information, prompt them to take Action by visiting the location and create content with the location as a background. Lastly, Share these experiences on their respective social media accounts. This research aims to find out how The Lodge Maribaya utilized Instagram as a promotional tool employing the AISAS concept, using the case study as a method. The primary data of this research consists of in-depth interviews with The Lodge's Marketing Communications Director, Fauziah Setia Rahayu. The results of the research show that at the Attention stage, The Lodge Maribaya focused on environmental education, exploiting trends, and developing market segmentation. At the Interest stage, The Lodge Maribaya have used the hashtag (#) feature in the caption for all rides and facilities, allowing them to carry out a recall with the same post with a different perspective. At the Search stage, using the hashtag feature makes it easier to search for related information. In the Action stage, The Lodge Maribaya employs a positive campaign tagline to attract visitors. Lastly, in the Share stage, The Lodge Maribaya encouraged their visitors to share their activities at The Lodge by tagging their official account.